Education for awakening : an eastern approach to holistic education - Nakagawa, Yoshiharu (Current perspectives in holistic education, 2025)
Eastern thought has significant potential for holistic education, providing rich ideas and various practices. However, integrating holistic education with Eastern thought has not been seriously considered in education. This work attempts to build an Eastern view of holistic education. Education for Awakening draws on diverse sources from Japanese philosophy (Zen Master Dōgen, D. T. Suzuki, Nishida Kitarō, and Izutsu Toshihiko), Hinduism (the Upaniṣads, the Bhagavad Gita, and Advaita Vedānta), Buddhism (the Buddha's teachings, Mahāyāna philosophies, and especially Zen), and Taoism (Lao Tzu and Chuang Tzu). It also discusses critical ideas from Confucianism, Tibetan Buddhism, and Sufism. Furthermore, it addresses Eastern sages such as Sri Ramakrishna, Swami Vivekananda, Rabindranath Tagore, Mahatma Gandhi, Sri Aurobindo, Ramana Maharshi, and Jiddu Krishnamurti. This work also tries to combine Western theories with the Eastern perspective. The Eastern view of holistic education has theoretical and practical aspects. Part I (Chapters 1-6) examines theoretical issues such as Eastern ways of thinking, five dimensions of reality, communication and communion, ecological and Buddhist views on relational reality, Hindu philosophy of liberation and the path of self-inquiry, and Taoist and Buddhist views on nature, language, silence, unlearning, and development. Part II (Chapters 7-10) explores four essential ways relevant to holistic education--awareness (mindfulness), action, compassion, and art. Education for Awakening brings insights into the nature of the self, states of consciousness, enlightenment, nondualism, and the wholeness of being.